Emergence and development trends of electronic banking in Serbia - Đekić Marija; Nikolić Miloš; Vesić Tamara (Trendovi u Poslovanju)
Global business changes and technology development open up new opportunities for banks to improve the quality of their services while reducing costs and increasing efficiency. One of the consequences of accelerated technological development and the efforts of banks to increase competitiveness is the emergence of electronic or internet banking. Electronic banking in Serbia began to be applied somewhere in 2003, but at a much slower pace than in developed countries. The main limitations of the insufficient use of electronic banking are related to the still insufficient use of the Internet and advanced technology, the resistance of the population to changes, the weak information system and the lack of information. Recently, the development of e-business in Serbia has been faster, and the assumptions are that this development will continue, especially in terms of the use of mobile banking. Banks should make efforts to create a culture of trust among customers and promote e-banking services, in order to influence public awareness of the positive aspects of this form of banking services. The paper describes the origin, current development and future perspectives of the use of electronic banking in the Republic of Serbia.